Editorial - Fusco Girard, Luigi (BDC. Bollettino Del Centro Calza Bini, 2017)
In our increasingly urbanized world, cities are facing important challenges (related to the economic, social and environmental crisis) referred to three great changes: demographic changes (population growth), structural changes (globalization) and environmental changes (climate change and pollution). Cities play a central role in the achievement of sustainable development. Cities (and in particular metropolitan cities) can represent a threat in the achievement of sustainable development but, at the same time, they can become the starting point to implement sustainable principles and goals. Many of Sustainable Development Goals (United Nations, 2015) can be achieved in the city because many problems are here concentrated. The growing urbanization and natural resource depletion require the identification of new models to increase urban productivity in environmental, financial, economic and social dimensions. They require exploring new ways of value creation ensuring, at the same time, economic prosperity, resource availability and wellbeing in a long-term perspective. It is necessary to rethink traditional models exploring and critically integrating alternative development models.